Marriage Dispute Resolution Through Judge Mediators and Its Implications for Child Development in the Religious Court of the Jurisdiction of the Banjarmasin Religious High Court - Mubarok Mubarok; Oyo Sunaryo Mukhlas; Ramdani Wahyu Sururie; Ending Solehudin; Muhammad Husni Abdulah Pakarti (Locus: Jurnal Konsep Ilmu Hukum, 2025)
The need for mediation is motivated by the accumulation of cases at the cassation level. Every year the cases that come to court are not decreasing, but are increasing. Meanwhile, the judge who has to resolve the case has limited capacity, so the cases that come in cannot be resolved quickly. This happened at the Religious Court in the Banjarmasin PTA area. Therefore, the concept of mediation is needed to reduce the problem of the accumulation of cases that occur at the religious court level, in terms of the benefit of children's growth and development. The research approach chosen uses an empirical juridical approach with a descriptive research method of analysis of theories of mediation and child protection and their implementation in judges' decisions regarding divorce in the Religious Courts in the Banjarmasin PTA area. Divorce has a negative impact on children's psychological development, because in general the psychological development of children whose parents are divorced is very disturbed, apart from that, the negative factor resulting from divorce is the lack of love and attention from both parents. Psychologically, parental divorce results in changes in behavior, responsibility and emotional stability.